Sameness and the self: philosophical and psychological considerations - Klein, Stan (Frontiers in Psychology, 2014)
In this paper I examine the concept of cross-temporal personal identity (diachronicity). This particular form of identity has vexed theorists for centuries – e.g., how can a person maintain a belief in the sameness of self over time in the face of continual psychological and physical change? I first discuss various forms of the sameness relation and the criteria that justify their application. I then examine philosophical and psychological treatments of personal diachronicity (for example, Locke’s psychological connectedness theory; the role of episodic memory) and find each lacking on logical grounds, empirical grounds or both. I conclude that to achieve a successful resolution of the issue of the self as a temporal continuant we need to draw a sharp distinction between the feeling of the sameness of one’s self and the evidence marshaled in support of that feeling.